When heme is low, copper kills cancer: leading edge - Linkermann, Andreas Günter (Cell, 2026)
Heme carries oxygen and is critical for the control of redox reactions. In this issue of Cell, Lewis and Gruber et al. demonstrate how low concentrations of heme destabilize complex IV of the respiratory chain to release copper and kill acute myeloid leukemia cells by cuproptosis.
Gesehen am 26.02.2026